Impact of Customer Engagement on Purchase Intention: A Promotional Online Survey on Instagram Account of @bandengisimrb - Shafa, Tharisa Putri; Kurniadi, Endrian; Yuniati, Ulfa (Binus Business Review, 2023)
The effective utilization of Instagram as a communication and promotional tool by Bandeng Isi MRB has the potential to impact online engagement significantly. By leveraging the accessibility and popularity of Instagram, producers can foster a sense of closeness and connection with their customers, ultimately increasing their interest in purchasing Bandeng Isi MRB products. The research aimed to examine the extent to which customer engagement influenced customers’ purchase intentions in response to Bandeng Isi MRB promotions. With a quantitative approach, the research employed an associative method to investigate the relationship between customer engagement and purchase intentions. The target population consisted of 763 customers who followed the Instagram account @bandengisimrb. To achieve an adequate sample size, the research used the Slovin Formula and determined that 161 individuals were needed. Then, data collected from the respondents were meticulously analyzed using the Statistical Package for Social Sciences (SPSS) through multiple linear regression analysis, with a significance level set at 5%. The findings reveal that various factors, including connection, interaction, satisfaction, retention, commitment, advocacy, and engagement, exert individual and combined effects on customers’ purchase intentions. The results underscore the significance of cultivating a strong and engaging online presence on platforms like Instagram for businesses like Bandeng Isi MRB as it can significantly influence consumers’ willingness to make purchases.